2018
DOI: 10.1111/medu.13774
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐medical majors in the humanities and social sciences: impact on communication skills and specialty choice

Abstract: Context Medical school admissions committees use a variety of criteria to determine which candidates to admit to their programmes. Effective communication is increasingly considered a key requisite to the practice of effective medicine. Medical students with pre‐medical backgrounds in the humanities and social sciences may be more likely to acquire skills relevant to patient‐centred communication, either prior to or during medical school. Objectives The purpose of this study was to investigate the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…A 2019 study showed that medical students with degrees in humanities or social science perform significantly better in interpersonal skills and communication compared to medical students with science degrees. 42 Shacklady et al found that students entering medicine just a few years older than age 21 years experienced a better transition from preclinical to clinical learning, 43 suggesting that life experience and social factors are influential at this age.…”
Section: Discussionmentioning
confidence: 99%
“…A 2019 study showed that medical students with degrees in humanities or social science perform significantly better in interpersonal skills and communication compared to medical students with science degrees. 42 Shacklady et al found that students entering medicine just a few years older than age 21 years experienced a better transition from preclinical to clinical learning, 43 suggesting that life experience and social factors are influential at this age.…”
Section: Discussionmentioning
confidence: 99%
“…Doukas et al (2015) for example, call for a more focused attention to medical school's admission process that encompasses "pre-professional readiness" of ethics and humanities, which might encourage "premedical learners to appreciate exposure to philosophy, anthropology, sociology, and psychology as valuable preparation toward medical education, including the groundwork of critical thinking skill building" (p. 739). Simultaneously, recent research has begun to explore how interdisciplinary training at the baccalaureate level impacts pre-professional students' understanding of health (Schwartz et al 2009;Crawford et al 2015;Baker et al 2017;Barron 2017;Berry and Lamb 2017;Charise 2017;Hirshfield et al 2019;Jones et al 2019;Wald et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also evidence that undergraduate education matters significantly, raising questions about the typical pipeline for medical school admissions from STEM fields. Hirshfield, Yudkowsky, and Park (2019) found that medical students who majored in humanities or social science scored higher in communication skills exams, and Olsen and Gebremariam (2020) found that humanities and interpretive social sciences majors entered and left medical school with higher empathy than their STEM peers. All of these trends demonstrate challenges in the values of the profession as well as in the context of medical work.…”
Section: Professional Socializationmentioning
confidence: 99%